Lynda Brown: The Shopper’s Guide to Organic Food - Hourani, Furugh (Petits Propos Culinaires, 1998)
Lynda Brown: The Shopper’s Guide to Organic Food: London, Fourth Estate, 1998: ISBN 1 85702 840-6: 370 pp, numerous useful lists, index, plb, £7.99.